Safety of pericardiocentesis in pulmonary arterial hypertension: a systematic review - Cabada-Garcia, Maria Jose; Rodriguez-Rivera, Jahir; Jerjes-Sanchez, Carlos; Castillo-Perez, Mauricio; Gutierrez-Gallegos, Paola; Martinez-Rodriguez, Ana Lucia; Paredes-Gutierrez, Enrique; Quevedo-Salazar, Renata Claudia; De Leon-Gutierrez, Humberto; Lopez-Cortes, Oscar David; Panneflek, Jathniel; Monjaras-Alvarado, Raul; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionControversy persists regarding the use of pericardial effusion drainage in patients with pulmonary arterial hypertension (PAH), as several studies report high rates of post-procedure morbidity and mortality.MethodsWe conducted a systematic review to evaluate the safety of pericardiocentesis (PC) in patients with PAH and a large or hemodynamically significant pericardial effusion. We focused on studies involving patients with PAH who presented with a large or hemodynamically significant pericardial effusion and underwent PH. Our primary objective was to evaluate the incidence of major periprocedural complications, and our secondary objectives were to identify the clinical presentation and echocardiographic findings.ResultsWe identified 35 patients across 16 studies. Connective tissue disease was the most common etiology of PAH. Drainage strategies during PC differed across studies. The overall mortality rate was 20%, and we identified pericardial decompression syndrome in 14% of patients. Dyspnea and peripheral edema dominated the clinical presentation. Echocardiographic findings of cardiac tamponade, particularly left-sided chamber collapse, appeared more frequently.DiscussionPC in patients with PAH carries a heightened risk of pericardial decompression syndrome and mortality. However, careful patient selection, echocardiographic guidance, gradual decompression, and continuous hemodynamic monitoring during the procedure may help improve outcomes.Systematic Review RegistrationPROSPERO 585310.